Experimental characterization of the out-of-plane behaviour of masonry infill walls made of lightweight concrete blocks - Marta Agante (2021)
Masonry infill walls are widely spread over the reinforced concrete buildings due to different demands. The buildings' thermal energy efficiency is a top priority nowadays since many of the existing building stock comprises buildings with low energy performance. The buildings' external envelope is undergoing a transformation with the vertical hollow concrete blocks' appearance with high thermal and acoustic demands. However, recent evidence from a strong earthquake shows that the masonry infill walls are quite vulnerable to out-of-plane loadings and were responsible for many casualties, injuries and economic losses. Based on that, this work's main objective is to study the out-of-plane (OOP) behaviour of masonry infills made with vertical hollow concrete blocks. The experimental campaign comprises the OOP testing of three full-scale infill walls made up of these masonry units, one of them as-built without previous damage, one with previous damage due to an earlier in-plane test and the third one retrofitted. All the tests consisted of applying the loading-unloading-reloading history of imposed displacements in the OOP direction through a uniformly distributed load. The results will be presented in terms of OOP force-displacement responses, damage evolution and energy dissipation capacity. The test results are compared to assess the previous damage effect and the retrofit technique's effectiveness. A final study is presented concerning the masonry unit and slenderness effect with other literature results.